Multiple Solutions for a Nonlocal Elliptic Problem Involving px, qx-Biharmonic Operator. (26th July 2021) - Zhang, Qi; Miao, Qing
Abstract : In this paper, using the variational principle, the existence and multiplicity of solutions for p x, q x -Kirchhoff type problem with Navier boundary conditions are proved. At the same time, the sufficient conditions for the multiplicity of solutions are obtained.